Bài 1: Tính
a) 5/3 + 4/3 =
b) 2/3 - 3/8 =
c) 6/5 x 3 =
d) 3/7 : 3/4 =
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(a,\dfrac{4}{7}+\dfrac{7}{2}\\ =\dfrac{8}{14}+\dfrac{49}{14}\\ =\dfrac{8+49}{14}\\ =\dfrac{57}{14}\)
\(b,\dfrac{5}{8}\times\dfrac{3}{2}\\ =\dfrac{5\times3}{8\times2}\\ =\dfrac{15}{16}\)
\(c,\dfrac{3}{2}\times\dfrac{5}{6}-\dfrac{2}{3}\\ =\dfrac{3\times5}{2\times6}-\dfrac{2}{3}\\ =\dfrac{15}{12}-\dfrac{2}{3}\\ =\dfrac{15}{12}-\dfrac{8}{12}\\ =\dfrac{15-8}{12}\\ =\dfrac{7}{12}\)
\(d,\dfrac{13}{15}+\dfrac{2}{5}:\dfrac{3}{4}\\ =\dfrac{13}{15}+\dfrac{2}{5}\times\dfrac{4}{3}\\ =\dfrac{13}{15}+\dfrac{2\times4}{5\times3}\\ =\dfrac{13}{15}+\dfrac{8}{15}\\ =\dfrac{13+8}{15}\\ =\dfrac{21}{15}\\ =\dfrac{7}{5}\)
`@` `\text {Ans}`
`\downarrow`
`1,`
`a)`
`-7/25 + (-8)/25`
`= (-7 - 8)/25`
`= -15/25`
`= -3/5`
`b)`
`6/13 + (-15)/39`
`= 18/39 + (-15)/39`
`= (18 - 15)/39`
`= 3/39`
`= 1/13`
`c)`
`5/7 + 4/(-14)`
`= 10/14 + (-4)/14`
`= (10 - 4)/14`
`= 6/14`
`= 3/7`
`d)`
`-8/18 + (-15)/27`
`= -4/9 + (-5)/9`
`= (-4-5)/9`
`= -9/9 = -1`
`2,`
`a)`
`3/5 + (-7)/4`
`= 12/20 + (-35)/20`
`= (12 - 35)/20`
`=-23/20`
`b)`
`(-2) + (-5)/8`
`= (-16)/8 + (-5)/8`
`= (-16 - 5)/8`
`= -21/8`
`c)`
`1/8 + (-5)/9`
`= 9/72 + (-40)/72`
`= (9-40)/72`
`= -31/72`
`d)`
`6/13 + (-14)/39`
`= 18/39 + (-14)/39`
`= (18 - 14)/39`
`= 4/39`
`e)`
`(-18)/24 + 15/21`
`= (-3)/4 + 5/7`
`= (-21)/28 + 20/28`
`= (-21 + 20)/28`
`= -1/28`
\(d,\dfrac{6}{5}-3:\dfrac{15}{4}=\dfrac{6}{5}-3\times\dfrac{4}{15}=\dfrac{6}{5}-\dfrac{4}{5}=\dfrac{2}{5}\)
\(b,\dfrac{2}{5}+\dfrac{4}{5}:4=\dfrac{2}{5}+\dfrac{4}{5}\times\dfrac{1}{4}=\dfrac{2}{5}+\dfrac{1}{5}=\dfrac{3}{5}\)
\(a,\dfrac{5}{8}+\dfrac{4}{3}=\dfrac{15}{24}+\dfrac{32}{24}=\dfrac{47}{24}\)
a) 3/7 + 3/4 - 1/2 =33/28-1/2=19/28
b) 6/11 + 2/9 x 12 =6/11+8/3=106/33
c) 5/7 - 8/5 : 4 =5/7-2/5=11/35
a) 3/7 + 3/4 - 1/2 = \(\dfrac{12}{28}+\dfrac{21}{28}-\dfrac{14}{28}=\dfrac{19}{28}\)
b) 6/11 + 2/9 x 12 = \(\dfrac{6}{11}+\dfrac{8}{3}=\dfrac{18}{33}+\dfrac{88}{33}=\dfrac{106}{33}\)
c) 5/7 - 8/5 : 4 = \(\dfrac{5}{7}-\dfrac{2}{5}=\dfrac{25}{35}-\dfrac{14}{35}=\dfrac{11}{35}\)
Bài 1:
Ta có: \(x-35\%\cdot x=\dfrac{1}{25}\)
\(\Leftrightarrow65\%\cdot x=\dfrac{1}{25}\)
\(\Leftrightarrow x=\dfrac{1}{25}:\dfrac{13}{20}=\dfrac{1}{25}\cdot\dfrac{20}{13}=\dfrac{4}{65}\)
Vậy: \(x=\dfrac{4}{65}\)
Bài 2:
a) Ta có: \(17\dfrac{2}{31}-\left(\dfrac{15}{17}+6\dfrac{2}{31}\right)\)
\(=17\dfrac{2}{31}-\dfrac{15}{17}-6\dfrac{2}{31}\)
\(=11+\dfrac{2}{31}-\dfrac{15}{17}\)
\(=\dfrac{5366}{527}\)
4:
a: =4/15-2,9+11/15=1-2,9=-1,9
b: \(=-36,75+3,7-63,25+6,3=10-100=-90\)
c: \(=6,5+3,5-\dfrac{10}{17}-\dfrac{7}{17}=10-1=9\)
d: \(=\dfrac{13}{25}\left(-39,1-60,9\right)=\dfrac{13}{25}\left(-100\right)=-52\)
e: =-5/12-7/12-3,7-6,3=-1-10=-11
f: =2,8(-6/13-7/13)-7,2=-2,8-7,2=-10
a) 9/3
b) 24/24
c)30/5
d) 12/21
Ghi cả cách làm ra, ko cần ghi quy đồng